Misalignment of global COVID-19 breastfeeding and newborn care guidelines with World Health Organization recommendations. Issue 2 (22nd December 2020) - Vu Hoang, Duong; Cashin, Jennifer; Gribble, Karleen; Marinelli, Kathleen; Mathisen, Roger
Abstract : Introduction: Recommendations for the clinical management of new mothers with suspected or confirmed COVID-19 and their infants are required. Guidance must weigh the risk posed by transmission of SARS-CoV-2 against the protection that maternal proximity and breastfeeding provide infants. Our aim was to review international COVID-19 guidance for maternal and newborn care, assessing alignment with WHO recommendations and the extent to which policy supported or undermined breastfeeding. Methods: Guidance documents from 33 countries on the care of infants whose mothers were suspected or confirmed as having COVID-19 were assessed for alignment with WHO recommendations regarding: (1) skin-to-skin contact; (2) early initiation of breastfeeding; (3); rooming-in; (4) direct breastfeeding; (5) provision of expressed breastmilk; (6) provision of donor human milk; (7) wet nursing; (8) provision of breastmilk substitutes; (9) psychological support for separated mothers; and (10) psychological support for separated infants. Results: Considerable inconsistency in recommendations were found. Recommendations against practices supportive of breastfeeding were common, even in countries with high infant mortality rates. None of the guidance documents reviewed recommended all aspects of WHO guidance. The presence of influential guidance conflicting with WHO recommendations and an undervaluing of the importance of maternal proximity and breastfeeding to infant health appeared to contribute to this poor alignment. Conclusion: Those developing guidance in the COVID-19 pandemic and other infectious disease outbreaks need to appropriately consider the importance of skin-to-skin contact, early initiation of breastfeeding, rooming-in and breastfeeding to maternal and infant physical and psychological health. In weighing the value of recommendations of others in future guidance development, countries should consider past reliability and value placed on breastfeeding. Recommendations against maternal proximity and breastfeeding should not be made without compelling evidence that they are necessary, and less harmful than maintaining dyad integrity.